Selection of the Most Suitable Alternative Fuel Depending on the Fuel Characteristics and Price by the Hybrid MCDM Method - SAYIN, CENK (MDPI, 2018)
In recent years, in order to increase the quality of life of people, energy usage has become very important. Researchers are constantly searching for new sources of energy due to increased energy demand. Engine tests are being conducted to investigate the feasibility of the new sources of energy such as alternative fuels. In the engine tests, engine performance, combustion characteristics and exhaust emissions are evaluated by obtaining the results. The effect of newly developed fuels on engine lifetime, safe transport and storage are also examined for fuel availability. In addition, the potential and the price of fuels are important in terms of sustainability. In these studies, laboratory environments are needed for experimental setups. It is difficult to determine the availability of the most suitable alternative fuel since numerous results are obtained in the engine tests and studies. This integrated model provides a great advantage in terms of time and cost. The physical and chemical properties of the fuel affect experimental results such as engine performance, combustion, and exhaust emission. The suggested model can be making the most efficient and eco-friendly fuel choice without the need for experimental studies by using physical and chemical properties of the fuel. It also can offer the best fuel for cost, safety and maintenance processes. In this study, animal fat biodiesel derived from waste animal fats and vegetable oil biodiesel produced from aspir-canola oils were investigated. Biodiesel fuels are mixed with diesel at 5%, 20%, and 50%, and nine different fuels prepared with three pure fuels, and six different fuel blends are compared. Before using these fuels in an experimental study, estimates are made about which fuels may be more advantageous in terms of many criteria. In the process, nine varied fuel specifications are taken as references such as calorific value, cetane number, oxygen content rate, fuel price, flash point, viscosity, lubricity, iodine number and water content. The criteria weights are determined with SWARA (Step-Wise Weight Assessment Ratio Analysis) from multi-criteria decision-making models, and MULTIMOORA (Multi-Objective Optimization on the basis of Ratio Analysis) is ranked according to fuels' characteristics from the best to the worst. While theoretically, the best fuel is ultimately VOB20, VOB50 and AFB20 were selected as the second fuel and the third fuel.
Keywords: multi-criteria decision making (MCDM); vegetable oil biodiesel; animal fat biodiesel; ANP; SWARA; MOORA; MULTIMOORA; fuel characteristics; DECISION-MAKING MODEL; DIESEL FUEL; EMISSION CHARACTERISTICS; EXHAUST EMISSIONS; ENGINE PERFORMANCE; BIODIESEL FUELS; CANOLA OIL; COMBUSTION; ESTERS; MULTIMOORA